Peripheral Immune Cell Populations Associated with Cognitive Deficits and Negative Symptoms of Treatment-Resistant Schizophrenia. - Emilio Fernandez-Egea; Petra E Vértes; Shaun M Flint; Lorinda Turner; Syed Mustafa; Alex Hatton; Kenneth G C Smith; Paul A Lyons; Edward T Bullmore (PLoS ONE)
Background Hypothetically, psychotic disorders could be caused or conditioned by immunological mechanisms. If so, one might expect there to be peripheral immune system phenotypes that are measurable in blood cells as biomarkers of psychotic states. Methods We used multi-parameter flow cytometry of venous blood to quantify and determine the activation state of 73 immune cell subsets for 18 patients with chronic schizophrenia (17 treated with clozapine), and 18 healthy volunteers matched for age, sex, BMI and smoking. We used multivariate methods (partial least squares) to reduce dimensionality and define populations of differentially co-expressed cell counts in the cases compared to controls. Results Schizophrenia cases had increased relative numbers of NK cells, naïve B cells, CXCR5+ memory T cells and classical monocytes; and decreased numbers of dendritic cells (DC), HLA-DR+ regulatory T-cells (Tregs), and CD4+ memory T cells. Likewise, within the patient group, more severe negative and cognitive symptoms were associated with decreased relative numbers of dendritic cells, HLA-DR+ Tregs, and CD4+ memory T cells. Motivated by the importance of central nervous system dopamine signalling for psychosis, we measured dopamine receptor gene expression in separated CD4+ cells. Expression of the dopamine D3 (DRD3) receptor was significantly increased in clozapine-treated schizophrenia and covaried significantly with differentiated T cell classes in the CD4+ lineage. Conclusions Peripheral immune cell populations and dopaminergic signalling are disrupted in clozapine-treated schizophrenia. Immuno-phenotypes may provide peripherally accessible and mechanistically specific biomarkers of residual cognitive and negative symptoms in this treatment-resistant subgroup of patients.